2015
DOI: 10.1097/cmr.0000000000000195
|View full text |Cite
|
Sign up to set email alerts
|

Microphthalmia transcription factor in malignant melanoma predicts occult sentinel lymph node metastases and survival

Abstract: Microphthalmia transcription factor (Mitf) is involved in melanocyte development and differentiation. We previously reported that Mitf expression, as detected by immunohistochemical analysis, is an independent prognostic marker in patients with intermediate-thickness melanoma. However, the clinical significance of Mitf expression in melanoma is not well delineated. In this prospective study, we attempted to demonstrate the correlation between Mitf expression in primary melanoma and the sentinel lymph node stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…For this reason the amplification of the MITF gene, with or without alterations of the corresponding protein expression levels, indicate patients who may benefit of treatment with inhibitors of histone deacetylase (HDAC), able to interfere with the expression of MITF protein [ 24 ]. To date, no predictive role for response to therapy has been documented, whereas MITF amplification has been implied on prediction of disease melanoma progression and disease prognosis [ 16 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason the amplification of the MITF gene, with or without alterations of the corresponding protein expression levels, indicate patients who may benefit of treatment with inhibitors of histone deacetylase (HDAC), able to interfere with the expression of MITF protein [ 24 ]. To date, no predictive role for response to therapy has been documented, whereas MITF amplification has been implied on prediction of disease melanoma progression and disease prognosis [ 16 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, cKIT gene was found amplified in 2–7% of primary MCM, with higher amplification in metastatic than in primary lesions [ 13 ]. Moreover, the amplification of microphthalmia-associated transcription factor ( MITF ) gene seems to play a role in melanoma progression [ 16 , 17 ], while the role of the genomic amplification for EGFR and cMET genes is less clear [ 18 ]. Finally, little is known on the interactions between mutations and amplifications of such candidate genes into the initiation and progression of the MCM lesions.…”
Section: Introductionmentioning
confidence: 99%
“…In a parallel effort, our group focused on the expression of MITF, a favorable molecular marker in cutaneous melanoma, in the primary tumors as a predictive factor of nodal involvement. Certainly, we showed that patients with higher MITF expression were less likely to have nodal spread (6). More specifically, we demonstrated in that report that none of the patients with MITF ≥50% had positive SLN.…”
Section: Discussionmentioning
confidence: 56%
“…Cytoplasmic staining was excluded from the analysis. MITF staining cut-off of ≥50% of the melanoma cells per slide (MITF≥50%) was used as an additional characteristic of the primary tumor based on our previous study (6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation